QIYĀS DALAM USHUL AL-SHARF: RELEVANSINYA SEBAGAI INSTRUMEN PRODUKTIF DALAM DERIVASI BENTUK-BENTUK KATA MODERN - Fitriani Sridar; Rahmaini; Baso Pallawagau (Al-Ma‘rifah, 2025)
This study aims to examine the concept of qiyās within the framework of ushul al-sharf and to analyze its relevance as a productive instrument in the derivation of modern Arabic vocabulary. The research is motivated by the need for the Arabic language to adapt to the rapid advancement of science and technology through the systematic creation of new terms that remain faithful to its morphological principles. Using a descriptive-analytical approach and library research method, this study explores the theoretical foundations of qiyās in classical linguistic works such as those of Sibawaih, al-Anbari, and al-Marzūqī, and compares them with contemporary derivational practices in modern Arabic terminology. The findings reveal that qiyās functions as a morphological analogy mechanism that enables the formation of new lexical items in a systematic and rule-governed manner. Consequently, qiyās serves not only as a normative linguistic method in classical Arabic grammar but also as an innovative and adaptive strategy in modern morphological development, contributing to the enrichment and modernization of Arabic vocabulary in various scientific and cultural fields.